Admission Control for Multiuser Communication Systems - Imran, Ali (My University, 2010)
During the last few years, broadband wireless communication has experienced very rapid growth in telecommunications industry. Hence, the performance analysis of such systems is one of the most important topics. However, accurate systems’ analysis requires first good modeling of the network traffic. Moreover, broadband wireless communication should achieve certain performance in order to satisfy the customers as well as the operators. Therefore, some call admission control techniques should be integrated with wireless networks in order to deny new users/services if accepting them will lead to degrade the network performance to less than the allowed threshold. This thesis mainly discusses the above two issues which can be summarized as follows. First issue is the traffic modeling of wireless communication. The performance analysis is discussed in terms of the quality of services (QoS) and also the grade of services (GoS). Different scenarios have been studies such as enhancing the GoS of handover users. The second issue is the admission control algorithms. Admission Control is part of radio resource management. The performance of admission control is affected by channel characteristics such as fading and interference. Hence, some wireless channel characteristics are introduced briefly. Seven different channel allocation schemes have been discussed and analyzed. Moreover, different admission control algorithms are analyzed such as power-based and multi-classes fuzzy-logic based. Some simulations analyses are given as well to show the system performance of different algorithms and scenarios.
Keywords: Admission control; Markov Models; Channel Allocation; Call blocking; Power Control; Propagation Models; Uplink and Downlink Radio Links; Fuzzy logic.; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|